Aktivitas Antiinflamasi Ekstrak Etanol Dan Fraksi Etil Asetat Daun Karet Kebo (Ficus elastica) Dengan Menggunakan Metode Spektrofometri UV-Vis - Suhaenah, Asriani; Nuryanti, Siska; Abidin, Zainal; Evatiara, Nur (Jurnal Fitofarmaka Indonesia, 2024)
Ficus is a species that is rich in polyphenolic compounds, such as flavonoids. These compounds are strong antioxidants that can aid in the prevention and treatment of various diseases caused by oxidative stress. They also protect cell structures, have anti-inflammatory properties, and can act as antibiotics. The aim of this study was to evaluate the anti-inflammatory properties of the ethanol extract and ethyl acetate fraction of rubber kebo (Ficus elastica) leaves using the Bovine Serum Albumin (BSA) protein denaturation method. The measurements were taken on a Uv-Vis spectrophotometer at a wavelength of 660 nm.  The study consisted of four experimental groups: a negative control, a positive control of diclofenac sodium, and test groups of ethanol extract and ethyl acetate fraction. The study revealed that the positive control (IC50) had an anti-inflammatory value of 9.2 μg/mL. Additionally, the ethanol extracts and ethyl acetate fractions of rubber kebo leaves (Ficus elastica) demonstrated anti-inflammatory activity with IC50 values of 31.24 μg/mL and 37.89 μg/mL, respectively. These findings suggest that the ethanol extracts and ethyl acetate fractions of rubber kebo leaves possess anti-inflammatory properties.